Cyclic liquefaction resistance of sand under a constant inflow rate - Adamidis, O; Anastasopoulos, I (ICE Publishing, 2022)
Cyclic resistance curves, derived through undrained element tests, are central to the study of liquefaction. Their use implies that water drainage is negligible during an earthquake. Nevertheless, a growing body of evidence suggests that this hypothesis is not realistic. In proximity to the interface of a liquefiable layer with an overlying lower permeability layer, upwards water flow can lead to localised, co-seismic pore volume increase. This paper aims to quantify the effects of pore volume increase on cyclic resistance curves. Cyclic triaxial experiments are presented, performed under undrained conditions and under conditions of volumetric expansion. A constant inflow rate is chosen for the sake of simplicity. Results show that even small inflow rates have a detrimental effect on cyclic resistance. A simplified methodology is developed, which can estimate cyclic resistance under constant water inflow rates, by assuming a superposition of isotropic unloading and undrained cyclic shearing. The presented results add to increasing evidence on how current liquefaction susceptibility assessments might not be conservative for layered deposits. In addition, they highlight significant aspects of soil response under partially drained conditions.